Educational intervention to raise awareness and foster responsibility for Chagas disease risk factors in the rural community of Texca, Guerrero, Mexico." - Alejandra Gabriela Bárcenas-Irabién; María Laura Sampedro-Rosas; Mariana C. De Alba-Alvarado; Margarita Cabrera-Bravo; Paz María Silvia Salazar-Schettino; Alexis Javier Garzón-Espinosa; Elia Torres-Gutiérrez; Martha Irene Bucio-Torres (Elsevier, 2024)
Problem considered: Chagas disease is a vector-borne parasitic infection considered of public health importance. For farmers and residents of endemic areas, vectors are part of their day to day life and they often lack awareness of their infectious potential, so the risk they pose is not a main concern in their lives. So far, existing measures set in place to eradicate the vector have not been effective long-term. Methods: In this study, a one-year program was designed and implemented to inform and assess the knowledge, attitudes, and perceptions of 81 parents or heads of household regarding the risk of transmission and prevention of Trypanosoma cruzi infection. The program aimed to raise awareness of the crucial role they play in the prevention and control of vectors associated with Chagas disease. Results: After educational interventions, a notable increase in the percentage of knowledge regarding the parasite, transmission factors, and Chagas disease was observed. Conclusion: This might suggest that properly implementing educational interventions within the population, with training from health professionals and through public programs, will allow for the reduction of infection risks. In the long term, it could significantly reduce the incidence of the disease in the region and state.